Integrating the CARERTAQDL Framework into Reflective ELT Practice in Nepal - Bhatta , Chandika (Journal of NELTA, 2025)
Reflective practice is central to teacher growth in English Language Teaching (ELT), yet many well-known models offered by Schön (1983), Kolb (1984), Gibbs (1988), Wallace (1991), and Moon (1999, 2004) struggle to capture the complex and multilingual realities of classrooms in Nepal. Farrell (2016) and Richards and Farrell (2005) have argued that reflection is especially vital in teacher professional development, but context-sensitive frameworks remain limited. This article introduces the CARER-TAQDL framework as a dialogic alternative. CARER (Concept, Application, Relevance, Evaluation, Reflection) supports teachers in structuring classroom decision-making, while TAQDL (Topic, Application/Action, Question, Decision, Learning) guides early career researchers in inquiry and project-based learning. Developed during doctoral study and later tested in the author’s own teaching, faculty workshops and research supervision, the framework has shown promise in making reflection more flexible, cyclical, and collaborative. Although grounded in Nepal, CARER-TAQDL also offers insights for other multilingual or resource challenged contexts. Practical examples are included to show how the framework can be used for reflective journals, practicum debriefs, and small-scale research design. By bridging pedagogy and inquiry, CARER-TAQDL aims to support teachers and researchers in navigating both classroom challenges and academic demands.